2002
DOI: 10.1080/08916930290028175
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Cases of Insulin Dependent Diabetes (IDDM) Occurring Three Years After Hemophilus Influenza B (HiB) Immunization Support Causal Relationship Between Immunization and IDDM

Abstract: Exposure to HiB immunization is associated with an increased risk of IDDM. NOD mice can be used as an animal model of vaccine induced diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 17 publications
2
28
2
1
Order By: Relevance
“…We previously proved the hemophilus vaccine causes IDDM in children and mice [1]. In a prior report we showed a rise in the incidence of IDDM in New Zealand following a massive hepatitis B vaccine program [3,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously proved the hemophilus vaccine causes IDDM in children and mice [1]. In a prior report we showed a rise in the incidence of IDDM in New Zealand following a massive hepatitis B vaccine program [3,10].…”
Section: Discussionmentioning
confidence: 99%
“…A large prospective clinical trial showed the hemophilus B vaccine caused clusters of cases of IDDM occurring between 36 to 48 months after vaccination [1]. The pertussis and MMR vaccine were associated with cluster of cases of IDDM occurring 24 to 48 months after immunization [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased immunization can explain both epidemics. Type 1 diabetes has previously been linked to immunization [18,19,40]. BCG vaccine has been previously associated with an increased risk of type 1 diabetes [1] and is now associated with an increased risk of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism is that type 1 and type 2 diabetes are polar opposite aberrant responses to immunization and other immune stimulants. Immune stimulation with vaccines causes some with low cortisol activity to develop an autoimmune disease including type 1 diabetes [18,19]. It is known that decreases in cortisol following adrenalectomy leads to increased rates of type 1 diabetes in mice [20].…”
Section: Discussionmentioning
confidence: 99%